Neutrosophic Clustering in Adaptive AI Learning for Students with Down Syndrome - Lutfi, Rania (MO.RI Publishing, 2025)
Students with Down syndrome respond positively to adaptive AI learning systems, but existing models struggle to effectively accommodate their unique challenges in working memory and attention control. These limitations stem from rigid clustering methods, which fail to personalize learning pathways according to the individual cognitive needs of students. This paper proposes a theoretical framework integrating Neutrosophic C-Means Clustering (NCM) into adaptive AI for special education. Grounded in cognitive theories on Down syndrome, the framework applies neutrosophic logic to refine membership functions truth, indeterminacy, and falsity and categorizes errors into conceptual, procedural, and attentional clusters. Rather than treating engagement as a fixed metric, this framework reinterprets indeterminacy as a dynamic state, allowing AI systems to adapt to variations in learner responsiveness and facilitate smoother human-AI interaction. While this remains a conceptual model, it sets the stage for future AI-assisted personalized learning systems, enabling educators and AI designers to collaborate in creating more flexible, responsive, and inclusive learning technologies. Furthermore, this paper highlights key ethical concerns, including bias risks in AI-driven education and maintaining human oversight to ensure fairness and inclusivity in AI-assisted learning environments.